Further Evidence of Mutational Heterogeneity of the XPC Gene in Tunisian Families: A Spectrum of Private and Ethnic Specific Mutations. (25th July 2013) - Ben Rekaya, Mariem; Jerbi, Manel; Messaoud, Olfa; Ben Brick, Ahlem Sabrine; Zghal, Mohamed; Mbarek, Chiraz; Chadli-Debbiche, Ashraf; Jones, Meriem; Mokni, Mourad; Boussen, Hamouda; Boubaker, Mohamed Samir; Fazaa, Becima; et al.
Abstract : Xeroderma Pigmentosum (XP) is a rare recessive autosomal cancer prone disease, characterized by UV hypersensitivity and early appearance of cutaneous and ocular malignancies. We investigated four unrelated patients suspected to be XP-C. To confirm linkage to XPC gene, genotyping and direct sequencing of XPC gene were performed. Pathogenic effect of novel mutations was confirmed by reverse Transciptase PCR. Mutation screening revealed the presence of two novel mutations g.18246G>A and g.18810G>T in the XPC gene (NG_011763.1). The first is present in one patient XP50NEF, but the second is present in three unrelated patients (XP16KEB, XP28SFA, and XP45GB). These 3 patients are from three different cities of Southern Tunisia and bear the same haplotype, suggesting a founder effect. Reverse Transciptase PCR revealed the absence of the XPC mRNA. In Tunisia, as observed in an other severe genodermatosis, the mutational spectrum of XP-C group seems to be homogeneous with some clusters of heterogeneity that should be taken into account to improve molecular diagnosis of this disease.